2022
DOI: 10.1101/2022.05.11.491470
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global early replication disrupts gene expression and chromatin conformation in a single cell cycle

Abstract: The early embryonic divisions of many organisms, including fish, flies and frogs are characterised by a very rapid S-phase caused by high rates of replication initiation. In somatic cells, S-phase is much longer due to both a reduction in the total number of initiation events and the imposition of a temporal order of origin activation. The physiological importance of changes in the rate and timing of replication initiation in S-phase remains unclear. Here we assess the importance of the temporal control of rep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Recent work has shown that increasing the rate replication rate in yeast by over expressing the rate‐limiting initiation factors leads to wide‐spread transcription reprograming. [ 118 ] The similarity of this phenotype to the phenotype of deletion of CAC1 , which encodes the large subunit of the CAF‐1 nucleosome chaperone, suggests that replicating the genome from too many replication forks at once causes a defect in nucleosome deposition, which in turn causes transcriptional defects.…”
Section: Why: Biological Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that increasing the rate replication rate in yeast by over expressing the rate‐limiting initiation factors leads to wide‐spread transcription reprograming. [ 118 ] The similarity of this phenotype to the phenotype of deletion of CAC1 , which encodes the large subunit of the CAF‐1 nucleosome chaperone, suggests that replicating the genome from too many replication forks at once causes a defect in nucleosome deposition, which in turn causes transcriptional defects.…”
Section: Why: Biological Significancementioning
confidence: 99%
“…[ 1 ] Furthermore, increased origin firing has genome‐wide effects on chromatin conformation and gene expression in yeast. [ 118 ] One proposed mechanistic explanation for this correlation is that different chromatin‐modification enzymes are active at different times in S phase, such that DNA replicated in early S phase in packaged in euchromatin and DNA replicated in late S phase is packaged in heterochromatin. [ 119 ] This model is supported by experiments showing that plasmids injected in to nuclei during early S phase are transcriptionally more active that those injected in late S phase.…”
Section: Why: Biological Significancementioning
confidence: 99%